Inheritance of Drought Tolerance During Germination and Early Growth in a Multiparental Population of Common Bean (Phaseolus vulgaris L.) (Agro Productividad, 2026)
Objective: (1) Estimate the genetic variables related to drought tolerance during germination of F₃ from a MAGIC common bean population, and (2) Classify the F3 as tolerant or susceptible to drought at an early stage.Design/methodology/approach: Seeds from 200 F3 of a MAGIC common bean population (designed as L-1, L-2, L-3… L-200) and their eight parents (R-bufa-80, R-bufa-60, T-negro, T-amarillo, PS-AZH-15-1, P-saltillo, USPT-WM-1 and Salinas) were used. A bioassay was established in the Plant Biophysics and Physiology Laboratory of the Colegio de Postgraduados, Montecillo, Mexico in July 2023. Seeds were germinated in Petri dishes at 27 ºC in a growth chamber. The experimental design was a simple lattice with two replications. The evaluated treatment consisted of germination in a PEG-6000 solution at -0.49 MPa for 72 h. The parents R-bufa-80, R-bufa-60, T-negro and T-amarillo were used as tolerant controls. Germination was quantified 24, 48 and 72 h after the establishment of the bioassay.Results: At 24 h, the germination percentage exhibited high heritability; however, it did not a quantitative inheritance pattern. For germination at 48 and 72 h, heritability was moderate, and for total length it was low. Neverthless, these traits displayed a phenotypic distribution consistent with quantitative inheritance. F3 L-184 appeared to exhibit transgressive segregation for germination at 24 h and for total length at 72 h. The evaluation of the complete multiparental population allowed the selection of F3 with the best and worst response to water deficit, based on their germination and early growth under PEG-6000 induced osmotic stress.Limitations on study/implications: Due to seed availability, the F3 were not evaluated under control (water) conditions; therefore, their response were compared with those of the parents previously characterized for drought tolerance.Findings/conclusions: Germination percentage and total length exhibited quantitative inheritance, except for germination at 24 h. F3 L-184, L-198, and L-106 can be classified as drought tolerant, whereas L-69 and L-182 can be classified as susceptible. This MAGIC population and their parents can be incorporated into breeding programs due to the range of identifiable responses.